2008
DOI: 10.1007/s12110-008-9042-4
|View full text |Cite
|
Sign up to set email alerts
|

Kin and Child Survival in Rural Malawi

Abstract: This paper investigates the impact of kin on child survival in a matrilineal society in Malawi. Women usually live in close proximity to their matrilineal kin in this agricultural community, allowing opportunities for helping behavior between matrilineal relatives. However, there is little evidence that matrilineal kin are beneficial to children. On the contrary, child mortality rates appear to be higher in the presence of maternal grandmothers and maternal aunts. These effects are modified by the sex of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 47 publications
2
51
1
1
Order By: Relevance
“…This supports the argument that kin help may be the cause of associations between kin and reproductive outcomes, but sufficiently detailed time−budget data are difficult to collect, so that it is rare to find datasets detailed enough to directly test whether kin help influences fitness outcomes. Further, while some researchers have proposed that kin help is the mechanism by which kin influence fertility outcomes, other researchers have argued that kin influence fertility through mechanisms other than (or in addition to) the help they provide; such as interactions with kin that propagate pro-natal norms (Newson et al 2005), competition for resources among kin that outweigh the positive effects of cooperation (Sear 2008;Strassmann 2011), and sexual or in-law conflict that may alter a woman's ideal fertility strategy (Borgerhoff, Mulder, and Rauch 2009;Leonetti, Nath, and Hemam 2007). To better understand these kin effects, we have developed a simple hypothesized causal pathway to test the mechanisms by which parents and in-laws are likely to influence fertility outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This supports the argument that kin help may be the cause of associations between kin and reproductive outcomes, but sufficiently detailed time−budget data are difficult to collect, so that it is rare to find datasets detailed enough to directly test whether kin help influences fitness outcomes. Further, while some researchers have proposed that kin help is the mechanism by which kin influence fertility outcomes, other researchers have argued that kin influence fertility through mechanisms other than (or in addition to) the help they provide; such as interactions with kin that propagate pro-natal norms (Newson et al 2005), competition for resources among kin that outweigh the positive effects of cooperation (Sear 2008;Strassmann 2011), and sexual or in-law conflict that may alter a woman's ideal fertility strategy (Borgerhoff, Mulder, and Rauch 2009;Leonetti, Nath, and Hemam 2007). To better understand these kin effects, we have developed a simple hypothesized causal pathway to test the mechanisms by which parents and in-laws are likely to influence fertility outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Sear and colleagues (2000) have shown that children in The Gambia who had reproductively active grandmothers were shorter than those whose grandmothers were postmenopausal. Another study looking at kin relationships in Malawi has shown a negative relationship between the presence of the maternal grandmother and infant mortality (Sear 2008). In this matrilineal society wealth is passed between female relatives, putting mothers and daughters in direct competition for resources.…”
mentioning
confidence: 99%
“…This has been observed in some farming populations such as the Mandinka in Gambia, the Maya in Mexico and the Chewa in Malawi, as well as in a 17th Century Qu eb ecoise population (Sear et al, 2002;Beise, 2005;Sear, 2008;Kramer, 2010).…”
Section: Introductionmentioning
confidence: 85%